Implementing ARCS Model to Design a Motivating Multimedia E-Book for Polytechnic ESL Classroom - Annamalai, Subashini (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
This paper describes the design of multimedia E-book (mE-book) based on the Keller’s ARCS Model of Motivational Design (1987). This paper also presented the implementation of mE-book as a motivating learning aid to promote ESL language learning in Polytechnic classrooms. Sixty (60) Polytechnic students experienced mE-book in their language classroom and their perceived motivation towards this learning material is measured using the Instructional Materials Motivation Survey (IMMS). This study is an attempt to adduce a scope for implementing multimedia in language learning in a motivating way for adult learners.